Fifty shades of black [videorecording (DVD)] - Wayans, Marlon; Hawk, Kali; Willard, Fred, 1939-2020-; Epps, Mike; Seymour, Jane, 1951-; Henderson, Florence (Open Road Films, 2016)
This spoof from the Wayans Brothers parodies the ultra-popular novel/film series Fifty Shades of Grey.